2022
DOI: 10.1186/s13756-022-01179-8
|View full text |Cite
|
Sign up to set email alerts
|

Low secondary attack rate after prolonged exposure to sputum smear positive miliary tuberculosis in a neonatal unit

Abstract: Background Several neonatal intensive care units (NICU) have reported exposure to sputum smear positive tuberculosis (TB). NICE guidelines give support regarding investigation and treatment intervention, but not for contact definitions. Data regarding the reliability of any interferon gamma release assay (IGRA) in infants as a screening test for TB infection is scarce. We report an investigation and management strategy and evaluated the viability of IGRA (T-Spot) in infants and its concordance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Previous studies on TB exposure at NICUs or nurseries in low TB burden countries have reported rare secondary attack rates (0–0.32%). 14 15 16 19 20 21 However, in a Thai study of nosocomial TB exposure in two NICUs, the overall incidence of TB disease in exposed infants up to one-year follow-up was 10.2% (24/236). Contact investigation beginning > 111 days after exposure was an independent risk factor for TB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies on TB exposure at NICUs or nurseries in low TB burden countries have reported rare secondary attack rates (0–0.32%). 14 15 16 19 20 21 However, in a Thai study of nosocomial TB exposure in two NICUs, the overall incidence of TB disease in exposed infants up to one-year follow-up was 10.2% (24/236). Contact investigation beginning > 111 days after exposure was an independent risk factor for TB.…”
Section: Discussionmentioning
confidence: 98%
“…However, previous studies on contact investigation in congregate settings related to neonates showed that protocols were modified according to expert opinions or epidemiologic circumstances, as in our study. 14 15 16 17 18 19 20 …”
Section: Discussionmentioning
confidence: 99%